40 km fiber transmission of squeezed light measured with a real local oscillator. (1st October 2022) - Suleiman, I; Nielsen, J A H; Guo, X; Jain, N; Neergaard-Nielsen, J; Gehring, T; Andersen, U L
Abstract: We demonstrate the generation, 40 km fiber transmission, and homodyne detection of single-mode squeezed states of light at 1550 nm using real-time phase control of a locally generated local oscillator (LO), often called a 'real LO' or 'local LO'. The system was able to stably measure up to around 3.7 dB of noise suppression with a phase noise uncertainty of around 2.5°, using only standard telecom-compatible components and a field-programmable gate array. The compactness, low degree of complexity and efficacy of the implemented scheme makes it a relevant candidate for long distance quantum communication in future photonic quantum networks.